Changes in Diaphragmatic Function Induced by an Increased Inspiratory Load Experienced by Military Divers: An Ultrasound Study - Rives, Sarah; Schmid, Bruno; Chaumet, Guillaume; Brégeon, Fabienne; Boussuges, Alain (Frontiers in Physiology, 2021)
Background: Inspiratory loading is experienced by military divers when they use rebreather device. Our objective was to assess the changes in diaphragm function induced by an increase in inspiratory load at values similar to those experienced by divers in real life. Methods: We recorded the excursion and the thickness of the right hemidiaphragm in 22 healthy male volunteers under inspiratory load conditions, using ultrasound in B- and M-mode. The measurements were performed at tidal volume and during breathing at 50% of inspiratory capacity. The breathing rate was regulated and similar in the various sessions with and without load. Results: The rebreather device used by French military divers leads to an increase in inspiratory load of close to 30 cmH20. Consequently, the session under load was performed using a device set to this threshold. Significant increases in the excursion and the thickening fraction of the diaphragm were observed between the sessions at tidal volume and at high volume. With addition of the inspiratory load, the excursion of the right hemidiaphragm increased significantly from 2.3 to 3.4 cm at tidal volume and from 3.9 to 4.7cm at high volume. The thickening fraction increased significantly from 30.4 to 76.6% at tidal volume and from 70 to 123% at high volume. The statistical analysis demonstrated that assessment of the changes of the thickening fraction during breathing at tidal volume was the most relevant marker to assess the impact of the inspiratory load on the diaphragm. Conclusion: Diaphragm ultrasound can be used to assess the changes in the diaphragm contraction pattern secondary to an increase in the respiratory load that can be generated by use a diving apparatus. The recording of the changes of the motion, and more importantly of the thickness of the diaphragm, during the breathing cycle is able to provide relevant information regarding the inspiratory load.